WOMEN TEACHERS FROM PRE-UNIVERSITY HAVING A SECOND JOB? - HĂISAN, Petronela Lăcrămioara; MONEA, Dan (Studia Universitatis Babeș-Bolyai. Educatio artis gymnasticae, 2021)
Introduction: Although there are some areas favored by male teachers, teaching is considered in the literature and traditionally a female profession. According to the latest studies in Romania, the percentage of women pre-university teachers has increased by 4% in recent years. Objectives: The main variable of interest in this study was to have a second job among female pre-university teachers in Romania and how this indicator affects their lives, especially health and leisure. Methodology: Data collection was performed online using the quality-of-life questionnaire based on the European Quality of Life Surveys structure. Of the 206 women respondents, 78 said they had a second job. Results: Following the analysis of demographic data, the average age of teachers included in the current study was 40.5 years. 63% are married, 20% are unmarried and 13% say they are divorced. The health condition is perceived as good by 50% of our respondents, most of them being in the age category 20-44 years. Most subjects (74%) stated that they have a hobby, although, unfortunately, 35% of the respondents did not confirm the preferred type of hobby. Conclusions: Although they have a second job, the continuous desire for education is high, certified by the fact that 63% of respondents take courses. Only 14% practice physical activity, which leads us to believe that people who have a second job when they have little free time, prefer activities that do not involve physical effort. Even though they have a second job, in terms of financial situation, 73% said that their monthly income is insufficient, and they are dissatisfied with their remuneration. REZUMAT. Ca profesoară în învățământul preuniversitar din România, poți avea un job secundar? Introducere: Deși există unele domenii favorizate de profesorii de gen masculin, predarea este considerată în literatura de specialitate și prin tradiție o meserie feminină. Conform ultimelor studii din România, procentul de femei cadre didactice din preuniversitar a crescut cu 4% în ultimii ani. Obiective: Principala variabilă de interes în acest studiu a fost aceea de a avea un al doilea loc de muncă în rândul profesorilor preuniversitari de gen feminin din România și modul în care acest indicator le afectează viața, în special sănătatea și timpul liber. Metodologie: Colectarea datelor a fost efectuată online utilizând chestionarul de calitatea vieții bazat pe structura European Quality of Life Surveys. Din cele 206 de femei respondente, 78 au declarat că au un al doilea loc de muncă. Rezultate: În urma analizei datelor demografice, vârsta medie a cadrelor didactice incluse în studiul actual a fost de 40,5 ani. 63%, sunt căsătoriți, 20% necăsătoriți și 13% au declarat că sunt divorțați. Starea de sănătate este percepută ca fiind bună de 50% dintre respondenții noștri, majoritatea acestora fiind în categoria de vârstă 20-44 de ani. Majoritatea subiecților (74%) au declarat că au un hobby, deși, din păcate, 35% dintre respondenți nu au confirmat tipul preferat de hobby. Concluzii: Deși au un al doilea loc de muncă, dorința continuă de educație este mare, certificată de faptul că 63 % dintre respondenți urmează cursuri. Doar 14% practică activitate fizică, ceea ce ne face să credem că persoanele care au un al doilea loc de muncă atunci când au puțin timp liber, preferă activități care nu implică efort fizic. Chiar dacă au un al doilea loc de muncă, în ceea ce privește situația financiară, 73% au declarat că veniturile lunare sunt insuficiente fiind nemulțumiți de remunerație. Cuvinte cheie: profesoare, al doilea loc de muncă, calitatea vieții, sănătate.